2015
DOI: 10.1007/s10008-015-2787-x
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary passivation studied by in situ scanning tunneling microscopy on microcrystalline copper

Abstract: Electrochemical scanning tunneling microscopy (ECSTM) was applied to analyze in situ the passivation of grain boundaries on microcrystalline copper in 0.1 M NaOH aqueous solution. Two types of boundaries, assigned to coherent twin and random grain boundaries, were studied in three different states of the copper surface: metallic after cathodic reduction of the air-formed native oxide film, passive after anodic polarization at 0.7 V vs. SHE to form the duplex Cu(I)/Cu(II) oxide film, and metallic after cathodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…In the case of Cu(I)/Cu(II) passivation (Figure 6b) [92,93], the passive film was found thicker at random boundaries than at coherent twin boundaries like for the Cu(I) passive film.…”
Section: [Insert Figure 4]mentioning
confidence: 92%
“…In the case of Cu(I)/Cu(II) passivation (Figure 6b) [92,93], the passive film was found thicker at random boundaries than at coherent twin boundaries like for the Cu(I) passive film.…”
Section: [Insert Figure 4]mentioning
confidence: 92%
“…The experiments were performed with microcrystalline samples obtained by cryogenic rolling after freezing in liquid nitrogen of highpurity cast electrolytic tough pitch copper. [22][23][24][25][26]65,66,[81][82][83] In order to ensure the relatively smaller grain size necessary for the microstructure to be included in the STM field of view, the annealing treatment for full recrystallization of the samples was limited in time and temperature of 1 min and 200°C, respectively. The resulting samples showed no preferential grain orientation, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that, in a 0.1 M NaOH solution, the passive film of Cu(I) oxide is thicker at grain boundaries than on the grains, and that no metal is preferentially consumed by transient dissolution at the grain boundaries [25,26]. Martinez-Lombardia et al investigated grain-dependent corrosion on microcrystalline copper in a 10 mM HCl aqueous solution and reported the dependence of grain orientation on corrosion [27].…”
Section: Introductionmentioning
confidence: 99%